IMPLEMENTASI MS. OFFICE EXCEL DAN GOOGLE FORMULIR DALAM MEMBANTU PENDATAAN POSYANDU PANDE MAS KUTA - Suryati, Kadek; Kartini, Ketut Sepdyana; Setiawan, I Made Dedy; Putri, Ni Wayan Suardiati; Krisna, Evi Dwi (Jurnal Widya Laksmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Pande Mas Posyandu is one of the community health posts located in Kuta District. The activities carried out include collecting information, recording data, processing data, and compiling it into a report containing information on the growth and development of infants, toddlers, pregnant women, as well as the provision of nutritious food for stunted children. The aim of this community service is to implement information technology such as Microsoft Excel and Google Forms to provide solutions to data recording issues at the posyandu. The implementation method of this community service includes several activities: identifying problems, developing training materials, conducting training for posyandu cadres, evaluation and measurement, data analysis, and report preparation. The conclusion that can be drawn is that through this community service activity, the implementation of Microsoft Excel and Google Forms at Pande Mas Posyandu in Kuta has led to an improvement in understanding, skills, and application of these tools by posyandu cadres. This shows that Microsoft Excel and Google Forms are technologies that can be used to process data and obtain information. The improved communication and delivery of child and maternal data have had a positive impact on increasing community participation in efficiently providing data on toddlers and pregnant women, and on ensuring that Posyandu activities are evaluated and reported in a timely manner.